Determinants of the mental health status of university students in Japan: comparison between pandemic and recession periods during the 7th wave of COVID-19 - Hirano, Yuko O. (Frontiers in Psychology, 2023)
Although the number of identified coronavirus disease 2019 cases and deaths has decreased, the repetitive crest-trough pattern of the spread of COVID-19 has yet to cease. The current situation may affect the mental health status of university students who are distracted in their academic and daily lives by the pandemic. This cross-sectional study aimed to identify the determinant factors of the mental health status of Japanese university students before and in the middle of the 7 th wave of the pandemic, one of the largest waves to be experienced in Japan. Method: A survey was administered to two groups of students during the recession period between the 6 th and 7 th waves (n=156) and during the 7 th wave of the pandemic (n=97). Results: T-tests showed no statistically significant differences between the two groups in Perceived Stress Scale (PSS) scores, while the COVID-19 anxiety scores (p<0.001) and General Health Questionnaire (GHQ) scores were significantly higher in the Pandemic period group (p=0.011). The multiple regression model indicated that PSS scores were the only determinant of GHQ scores in the Pandemic period group. Discussion: The results indicate that stressful life events, such as the COVID-19 pandemic and daily hassles, which are measured by the PSS, affect students' mental health differently. Therefore, the author submits that school counselors should provide counseling to students to reduce anxiety caused by daily hassles, during recession and pandemic periods. Students also require assistance with the reduction of stress and anxiety caused by daily hassles, regardless of the pandemic situation.